Pengaruh Brand Image dan Gaya Hidup Hedonis terhadap Minat Beli IPhone pada Mahasiswa STIE Bima - Nunung Andriani; Ismunandar Ismunandar; Ovryadin Ovryadin (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
This study aims to examine whether there is a correlation between the hedonistic lifestyle of STIE Bima students and their aspiration to purchase an iPhone. The hedonistic lifestyle, which focuses on the pursuit of pleasure and instant gratification, often drives individuals to acquire luxury and prestigious items such as the iPhone. However, issues related to the product, such as fast battery drainage, poor performance, and blocked IMEI, have been documented by users. These problems can affect the brand image and purchasing intentions. Furthermore, the temporary nature of hedonistic pleasure causes consumers to continually seek new products to fulfill their emotional desires, which could influence their purchasing decisions. Additionally, negative perceptions of a product’s value, price, or quality may lead consumers to hesitate in making a purchase. Therefore, it is essential to understand how the hedonistic factor interacts with the intention to buy a specific product, particularly among students who are often the primary consumers of electronic products like the iPhone. This study uses a quantitative method with an associative research strategy to explain the relationship between a hedonistic lifestyle and purchase intention. A total of 96 STIE Bima students were selected as the sample, using the Lemeshow algorithm. Data were collected through questionnaires, direct observation, and literature review. Data analysis was performed using various statistical methods, including validity and reliability tests, classical assumption tests (such as normality, multicollinearity, heteroscedasticity, and autocorrelation), as well as multiple linear regression analysis. t-tests (both partial and simultaneous) were used to test the impact of each variable on purchase intention. Correlation coefficients were used to measure the strength of relationships between the variables studied. The results of this study are expected to provide insights into how a hedonistic lifestyle influences iPhone purchasing decisions among students.